ENSURING THE RESISTANCE OF CONCRETE UNDER CONDITIONS OF AGGRESSIVE ENVIRONMENT - Utemuratov S. M.; Allasugirov N. B. (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the increase in the corrosion resistance of a concrete surface under the action of external aggressive factors by modifying it with protective coatings.